O Potencial Distributivo do Imposto de Rendapessoa Física (IRPF) - Sergei Soares; Fernando Gaiger Silveira; Claudio Hamilton dos Santos; Fábio Monteiro Vaz; André Luis Souza (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– This text argues for higher Personal Income Tax levels. We show that, for all countries for which tax information is available, Brazil is the one in which Personal Income Tax collection as a percentage of the gross tax burden is the lowest. Personal Income Taxes account for about 6% of the Gross Tax Burden, slightly more than 2% of GDP, and slightly more than 4% of family income (according to the PNAD household survey). We show that this is due both to the fact that tax brackets are so high so as to exempt 85% of income earners from paying any income tax and the fact that our highest tax bracket is only 27.5%, which is lower than the maximum tax bracket of almost all countries for which tax information is available. Using Household and Expenditure Surveys, we estimate the Personal Income Tax Concentration Coefficients at between 89 and 92, which show a very progressive tax schedule. We also estimate that families who live on self employment and business income evade or avoid 80% of their personal income tax liabilities but that families who live off employment income evade or avoid only 20%. Finally, we analyze the impact of a series of theoretical changes in Personal Income Tax rules and conclude that they would approximately double Personal Income Tax collection. If the additional revenue were compensated by a reduction in a regressive tax, such as Contribuiç\~ao para o Financiamento da Seguridade Social (Cofins), so as to hold the total Tax Burden constant, the result would be a 2,3 point fall in the Gini coefficient.
Keywords: H23; H24; 330